Executive function predicts the development of play skills for verbal preschoolers with autism spectrum disorders. Issue 12 (18th February 2016) - Faja, Susan; Dawson, Geraldine; Sullivan, Katherine; Meltzoff, Andrew N.; Estes, Annette; Bernier, Raphael
Abstract : Executive function and play skills develop in early childhood and are linked to cognitive and language ability. The present study examined these abilities longitudinally in two groups with autism spectrum disorder—a group with higher initial language ( n = 30) and a group with lower initial language ability ( n = 36). Among the lower language group, concurrent nonverbal cognitive ability contributed most to individual differences in executive function and play skills. For the higher language group, executive function during preschool significantly predicted play ability at age 6 over and above intelligence, but early play did not predict later executive function. These results suggested that factors related to the development of play and executive function differ for subgroups of children with different language abilities and that early executive function skills may be critical in order for verbal children with autism to develop play. Autism Res 2016, 9: 1274–1284 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.